Rancang Bangun Alat Pendeteksi Alkohol Portabel Pada Pernafasan Manusia Menggunakan Arduino Nano - M. Alparizi Pebers; bayu wahyudi; Patrisius Kusi Olla; Diah Ningtias (Elkom : Jurnal Elektronika dan Komputer, 2022)
Article history: Received 30 Mei 2020 Received in revised form 2 Juni 2020 Accepted 10 Juni 2020 Available online 12 Juni 2020 ABSTRACT Alcohol is the common name for organic compounds that have a hydroxyl group attached to carbon and hydrogen atoms. The alcohol that is commonly found in liquor is ethyl alcohol or it is also called ethanol, but it is usually referred to as alcohol alone. Drinks with an alcohol content of 40% can lose consciousness, leading to accidents for alcohol-affected drivers. To detect alcohol in the body using an alcohol tester. Researchers tried to make a measuring instrument for alcohol levels in the body using several components such as Arduino nano, MQ 3 sensor, OLED, charger module, battery, resistor, push button, and buzzer. The design of a portable alcohol level detector through breath can work well, namely the results of the reading of alcohol levels in the body by the MQ-3 sensor through the breath and displayed on the Oled Display in units of% BAC (Blood Alcohol Concentration), in the sample comparison of the alcohol level reading between Final project tool with a comparison tool alcohol tester obtained the percentage difference in an average of 0.01% BAC. Keywords: Alcohol, Arduino Pro Micro, MQ-3 Sensor, OLED, Charger Module, Battery, Resistor, Push Button, and Buzzer